Comparative Evaluation Of Indigenous Chicken Reared Under Different Systems For Egg Quality Traits - Nagarahalli, Rajakumar; Narasimhamurthy, H. N.; Gopinath, C. R.; Umakantha, B.; Veeregowda , B.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was conducted to evaluate the indigenous chicken (pertaining to Bangalore Division of Karnataka) reared under intensive and scavenging system for external and internal egg quality traits. The external egg quality traits considered were egg weight, shell colour and shape index. The internal egg quality traits include albumin index, yolk index, shell thickness and Haugh unit score. The frequency of eggs pertaining to different shell color were 23.22, 36.29 and 40.49 per cent for creamy, light brown and brown, respectively under intensive system and 16.90, 44.46 and 38.64 per cent for creamy, light brown and brown, respectively under scavenging system. The Mean values recorded were 40.61±0.48 and 43.16±0.31g for egg weight; 76.04±0.40 and 74.12±0.56 for shape index, when birds were reared under intensive and scavenging system respectively. The average values of 0.080±0.002 and 0.087±0.001 for albumin index; 0.41±0.007 and 0.42±0.004 for yolk index; 74.36±1.009 and 78.01±0.49 for Haugh unit score; 0.37±0.003 and 0.33±0.003 for shell thickness, under Intensive and Scavenging system, respectively. The egg quality traits did not differ significantly between districts within the system of rearing. However significant (P<0.05) differences were observed for all the traits between the systems of rearing, except for egg weight, albumin index and albumin weight.